Analysis of the Learning Curve of Surgeons without Previous Experience in Laparoscopy to Perform Robot-Assisted Radical Prostatectomy - Felipe Monnerat Lott; Deborah Siqueira; Hermano Argolo; Bernardo Lindberg Nóbrega; Franz Santos Campos; Luciano Alves Favorito (Advances in Urology)
Objective. To assess the learning curve in robot-assisted radical prostatectomy (RARP) performed by surgeons without previous experience in laparoscopic prostatectomy. Materials and Methods. We analyzed 119 patients submitted to RARP performed by two surgeons without previous experience in laparoscopic prostatectomy, with emphasis on the relevant outcomes such as continence, erectile function, and oncologic control with a minimum follow-up of 24 months. We used Fisher’s exact test and the chi-square test to investigate the existence of a relationship between the variables and analysis of variance (ANOVA) to verify possible statistically significant differences between groups, at the 5% level. Results. The patients’ age varied from 41 to 72 years (mean = 61.09), with 68 (57.14%) cases having intermediate or high risk. There was a consistent decline in operative time. Of the 119 patients, 80.67% were continent 6 months after surgery and 89.07% 12 months afterward, while 35.29% were potent 6 months after surgery and 60.50% 12 months following surgery. Twelve months after surgery, the trifecta outcome rate was 51.26% and the pentafecta rate was 31.09%. There was progressive postoperative improvement and maintenance of continence and sexual potency until the last patient was operated in our sample. Conclusions. Robot-assisted radical prostatectomy does not require previous experience in laparoscopic radical prostatectomy, but the learning curve is not short to achieve the plateau.